(untitled) (Journal of Artificial Intelligence & Research, 2024)
Artificial intelligence (AI) has revolutionized various fields of medicine, and dentistry is no exception. This paper explores the advancements and applications of AI in dental imaging, focusing on image analysis, segmentation, and interpretation. AI techniques such as machine learning and deep learning have enabled remarkable progress in diagnosing dental conditions and planning treatments. This abstract provides an overview of key developments and their implications in dental practice and research.